Reaching out to the West: An assessment of Chinese students' views regarding foreign-delivered university programs in China - Willis, Mike (Journal of teaching in international business, 2010)
This article identifies the views and expectations of Chinese students located in nine cities in China and Hong Kong in regard to the delivery of foreign degree programs within China. This delivery mode is becoming a common form of educational delivery and augments other modes of international activity such as study abroad and distance education. The research has found that students wanted a relatively unadapted course, delivered in English by foreign academics, with a high level of academic and administrative servicing in China. They did not like subjects which had been overly adapted for the Chinese market, since these were viewed to be somewhat lacking in authenticity. However, some very minor areas of adaptation were required to meet some specific local requirements, but in essence students wanted courses which were a close replication of what it would be like to study in the foreign university location, whether it be in America, Australia, or Europe. The value of this research is that it identifies the desire of students for relatively unadapted foreign programs in China. This finding is of use to foreign universities planning courses and programs in China and also adds to the debate about the adaptation or standardization of services in a Chinese context.